The Meassurement of the Equilibrium Real Exchange Rate. A New Econometric Approximation - Carrera, Jorge Eduardo ([Actas])
To determine the deviation of the real exchange rate (RER) with respect to some equilibrium level is of great importance for economic policy. However, the measurement of the RER as well as the determination of its equilibrium level are controversial matters. In this work we present the two main approaches in the literature of the Equilibrium Exchange Rate: the Purchasing Power Parity hypothesis and the theory of the "fundamentals". In this paper, we propose a VECM methodology for the determination of the equilibrium RER in the framework of the "fundamentals" approach. Then, we suggest a methodology (a "rolling" VECM estimation) to check the stability of the parameters that at the same time improves on the VECM estimation. Finally, we suggest proposals to improve the theory of "fundamentals" giving greater weight to the dis-equilibriums in the labor market